Long-term impact of chronic pelvic pain on quality of life in women with and without endometriosis - Sayuli Bhide; Rebecca Flyckt; Meng Yao; Tommaso Falcone (Clinical and Experimental Obstetrics & Gynecology, 2021)
Background: Chronic pelvic pain (CPP) has a significant impact on patients’ health-related quality of life (HRQoL). Endometriosis is a common cause of CPP. Data is lacking on long-term HRQoL outcomes in patients with endometriosis-associated chronic pelvic pain (EACPP) versus other causes of chronic pelvic pain (OCPP). Methods: In this retrospective single-survey study, 198 patients completed the EHP-30 and the patient-reported outcomes measurement information system (PROMIS) Global Health validated questionnaires to assess health-related quality of life (HRQoL) 8–10 years after index surgery. Results: Demographic comparison revealed significant differences in racial demographics and disability status between the EACPP and OCPP groups. There was no significant difference in EHP-30, PROMIS Global Physical, or Global Mental scores between the two groups. Patients with lower stage endometriosis (stage I/II) reported diminished HRQoL in the EHP-30 and Global Physical scores as compared to patients with higher stage (stage III/IV) endometriosis or OCPP. Additionally, no differences were found between incidence of abuse history and EHP-30 and PROMIS scores between the two groups. Higher age and higher PROMIS Global Physical scores were associated with lower pain and higher HRQoL scores on the EHP-30. Persistently high rates of sexual dysfunction were seen across both groups. Discussion: This study demonstrates that women with EACPP and OCPP appear to have similar natural histories and quality of life on long term follow-up. Race, age, disability, and physical health status may play key roles in perceived quality of life. The high rate of persistent sexual dysfunction is concerning and requires increased clinician intervention.